The 5-HT6 receptor antagonist idalopirdine potentiates the effects of donepezil on gamma oscillations in the frontal cortex of anesthetized and awake rats without affecting sleep-wake architecture. (February 2017) - Amat-Foraster, Maria; Leiser, Steven C.; Herrik, Kjartan F.; Richard, Nelly; Agerskov, Claus; Bundgaard, Christoffer; Bastlund, Jesper F.; de Jong, Inge E.M.
Abstract: The 5-HT6 receptor is a promising target for cognitive disorders, in particular for Alzheimer's disease (AD). The high affinity and selective 5-HT6 receptor antagonist idalopirdine (Lu AE58054) is currently in development for mild-moderate AD as adjunct therapy to acetylcholinesterase inhibitors (AChEIs). We studied the effects of idalopirdine alone and in combination with the AChEI donepezil on cortical function using two in vivo electrophysiological methods. Neuronal network oscillations in the frontal cortex were measured during electrical stimulation of the brainstem nucleus pontis oralis (nPO) in the anesthetized rat and by an electroencephalogram (EEG) in the awake, freely moving rat. In conjunction with the EEG study, we investigated the effects of idalopirdine and donepezil on sleep-wake architecture using telemetric polysomnography. Idalopirdine (2 mg/kg i.v.) increased gamma power in the medial prefrontal cortex (mPFC) during nPO stimulation. Donepezil (0.3 and 1 mg/kg i.v.) also increased cortical gamma power and pretreatment with idalopirdine (2 mg/kg i.v.) potentiated and prolonged the effects of donepezil. Similarly, donepezil (1 and 3 mg/kg s.c.) dose-dependently increased frontal cortical gamma power in the freely moving rat and pretreatment with idalopirdine (10 mg/kg p.o.) augmented the effect of donepezil 1 mg/kg. Analysis of the sleep-wake architecture showed that donepezil (1 and 3 mg/kg s.c.) dose-dependently delayed sleep onset and decreased the time spent in both REM and non REM sleep stages. In contrast, idalopirdine (10 mg/kg p.o.) did not affect sleep-wake architecture nor the effects of donepezil. In summary, we show that idalopirdine potentiates the effects of donepezil on frontal cortical gamma oscillations, a pharmacodynamic biomarker associated with cognition, without modifying the effects of donepezil on sleep. The increased cortical excitability may contribute to the procognitive effects of idalopirdine in donepezil-treated AD patients. Highlights: Idalopirdine augments the effects of donepezil on cortical gamma oscillations. Idalopirdine does not modify sleep-wake patterns nor the effects of donepezil. 5-HT6 R antagonism augments effects of cholinesterase inhibition in the cortex. Increased cortical excitation may add to procognitive effects of idalopirdine.